Symbolic decentralization and political identity: Aspiration for special status in Surakarta - Riska Nofharina Lutfiah; Titin Purwaningsih; I Kadek Sudiarsana (Faculty of Social and Political Science, Universitas Airlangga, 2026)
The renewed pursuit of special status for Surakarta within Indonesia’s symbolic decentralization reflects the demand for recognition based on historical context, cultural identity, and symbolic legitimacy. This research examines how historical narratives and cultural identity are used as political strategies to support claims for special regional status, drawing on political symbolism and social identity theories. Using a qualitative case study approach, the analysis reviews regulations, academic literature, national media, and public responses on digital platforms. The findings show that symbols and historical narratives have not yet aligned, mainly due to weak connections between local and institutional actors and negative portrayals of the palace elite. Consequently, the main challenges are not only symbolic but also structural, regulatory, and political, which limit the translation of historical legitimacy into policy support. This study concludes and highlights the critical role of political symbolism, collective identity, public opinion, and legal frameworks in developing inclusive policies. However, today’s governance systems focus on administrative aspects rather than historical and symbolic considerations.